Do parties make a difference? A review of partisan effects on health and the welfare state. (23rd July 2019) - Falkenbach, Michelle; Bekker, Marleen; Greer, Scott L
Abstract: Background: Do political parties matter to health? Do they affect population health either directly or through welfare states' social policies and the eligibility, affordability and quality of health systems? And if they do, how? These are crucial questions if we are to understand health politics or shape public health policy, particularly given the changing landscape of political parties, party dominance in the executive and the mediating influence of the legislature. Methods: Using a systematic approach, this review examines 107 peer-reviewed articles and books published after 1978 focusing on high-income countries asking the overarching question: Do political parties matter to health and the welfare state? Results: The literature relating parties to health directly was surprisingly thin, thus, the welfare state was used as a 'proxy' variable. An overwhelming majority of the literature sample suggests that Left parties are inclined to expand the welfare state without cutting benefits, while the Right does not expand and tends to reduce benefits. There was an inflection in the 1980s when Left parties shifted from expansion to maintaining the status quo. Conclusion: Considering current health trends in the form of measles outbreaks, the 'Deaths of Despair', the rise of previous eradicated infectious diseases and the declining health expectancy rates in some Western countries as well as the rise of Populist Radical Right parties in office we question the current partisanship thesis that political parties matter less and less.